Relationship between VEGF to PEDF ratio and in-hospital mortality in acute respiratory distress syndrome patients - Qifeng Luo; Ningning Shen; Jingtian Liang; Xichun Qin; Shoujie Feng; Yuting Chen; Lei Xu (Scientific Reports)
Abstract Acute respiratory distress syndrome (ARDS) has a high mortality rate worldwide; thus, identifying death risk factors related to ARDS is critical for risk stratification in patients with ARDS. In the present study, we conducted a single-center retrospective cohort analysis. Out of 278 patients with ARDS admitted from January 2016 to June 2022, 226 were included in this study. The patients were classified based on whether they were alive or dead during hospitalization. Their demographic and laboratory data and results were analyzed by performing a standard statistical analysis. Patients in the death group were older, with worse respiratory functions and blood biochemistry than those in the non-death group. Moreover, statistically significant differences were observed in the levels of vascular endothelial growth factor (VEGF) and pigment epithelium-derived factor (PEDF) between the two groups. Multivariate stepwise logistic regression analysis showed that the VEGF/PEDF ratio was strongly associated with the risk of death. The area under the curve of the VEGF/PEDF ratio was 0.829 (95% confidence interval: 0.772–0.885; P < 0.001), sensitivity was 86.3%, and specificity was 68.0%. Therefore, a VEGF/PEDF ratio is positively correlated with the risk of death in patients with ARDS.